Systematic Review: Effectiveness of Self-Monitoring-Based Behavior Modification in Increasing Senior High School Responsibility for Learning - Edigius Paulus Banu; Henny Indreswari; Arbin Janu Setiyowati (G-Couns: Jurnal Bimbingan dan Konseling, 2026)
Learning responsibility is essential for academic success among senior high school students, yet many struggle with self-regulation due to technological distractions and low motivation. Self-monitoring-based behavior modification offers a promising intervention to address this issue. This systematic review evaluates the effectiveness of self-monitoring interventions in enhancing learning responsibility among senior high school students. Following PRISMA guidelines, a systematic search was conducted across six databases (ScienceDirect, SpringerLink, Google Scholar, Scopus, Garuda, and ResearchGate) for peer-reviewed articles published between 2015-2025. Studies examining self-monitoring interventions targeting learning responsibility or related constructs in senior high school settings were included. Thematic synthesis was employed to analyze findings. From 312 initially identified records, 47 studies met the inclusion criteria. Findings consistently demonstrate that self-monitoring techniques—including self-recording, checklists, and digital tracking significantly improve students' discipline, time management, and academic engagement. Grounded in Social Cognitive Theory, these interventions enhance self-efficacy and self-regulation. Effective implementation requires structured teacher guidance and supportive learning environments, while challenges include limited parental involvement and technological barriers. Self-monitoring is an effective strategy for fostering responsibility for learning in senior high school students. Future research should employ longitudinal designs to assess sustained impacts across diverse educational contexts. Keywords: behavior modification, self-monitoring, student responsibility